Differential significance of early surgical complications for acute and long-term recurrence-free survival following surgical resection of hepatocellular carcinoma: do comorbidities play a role?. Issue 9 (September 2017) - Khandoga, Andrej; Drefs, Moritz; Schoenberg, Markus; Schiergens, Tobias; Frenes, Katharina; op den Winkel, Mark; Trumm, Christoph; Angele, Martin K.; Guba, Markus; Werner, Jens; Rentsch, Markus
Abstract : Background: Postoperative complications of Clavien–Dindo grade 3 or more are of prognostic significance in patients who undergo liver resection for hepatocellular carcinoma (HCC). However, perioperative mortality and patient comorbidities represent relevant factors that interfere with postoperative long-term survival. To clarify this, a retrospective single-center study was carried out. Patients and methods: Patient data were prospectively collected in a continuously updated liver resection database. Overall, 184 consecutive patients who underwent liver resection for HCC with a curative intent between March 2003 and December 2013 were selected for the study. The patients were assigned to two groups according to the presence or absence of postoperative complications. Pre-existing comorbidities, perioperative mortality, surgical outcome, and long-term survival data were analyzed. Results: Postoperative complications requiring revision surgery were identified in 17.4% of the patients. The in-house mortality rate was 4.8%. Compared with patients without complications, patients with complications were older and had significantly more pre-existing comorbidities, more advanced tumors, more intrahepatic metastasis, longer operation times, greater blood loss, and more extensive resections. The overall 5-year survival rates were 40.1 and 52.5% in patients with or without postoperative complications, respectively. The corresponding 5-year recurrence-free survival rates were 46.3 and 46.7% (perioperative mortality excluded). Multivariate analysis showed that elevation of the Charlson Comorbidity Index was associated independently with decreased overall and recurrence-free survival. Conclusion: In patients with HCC, posthepatectomy complications are confirmed to have predictive value. However, closer analysis and exclusion of perioperative mortality effects show an independent impact of pre-existing comorbidities on long-term overall und recurrence-free survival. Abstract : Supplemental Digital Content is available in the text.